ANALISIS ONGKOS PENDIDIKAN PERGURUAN TINGGI DALAM MENYONGSONG PERGURUAN TINGGI NEGERI MENJADI BHMN - Hendra Hendra; Yazmendra Rosa; Arwizet K (Jurnal Teknik Mesin, 2004)
Cost production in the education is the important. Education Quality influence by performance in personal and facility. The good personal and facility is affecting cost production (education). Height quality education consumption cost produced is more expensive. To cost education can be minimization. with the analyses cost production (education) example calculated overhead, cost operational and etc. Level of this education fare can be applied by paying attention ability of consumer so those process studies stand at bay with quality of good education.